How constant is constant elasticity of substitution? Endogenous substitution between clean and dirty energy - Ara Jo; Alena Miftakhova (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
The degree of substitutability between clean and dirty energy plays a central role in leading economic analyses of optimal environmental policy. Despite the importance, a constant and exogenous elasticity of substitution has been a dominant theoretical approach. We challenge this assumption by developing a dynamic general equilibrium model with an endogenous elasticity of substitution that interacts with the relative share of clean inputs in the economy. We find strong dynamic feedback effects arising from endogenous substitution capacity that amplifies the impact of directed technical change and accelerates the transition to a green economy.
Keywords: Q40; Q55; Q54; O33; 330; elasticity of substitution; directed technical change; climate change